2015
DOI: 10.1093/aobpla/plu091
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of soil extracts can be used to investigate fine root depth distribution of trees

Abstract: Knowledge of a tree species or cultivar's fine root distribution is important. However, the time and resource requirements of established soil core based methods where live from dead root determination is required, act as a constraint to large studies. We developed a method to determine live fine root DNA density for mango (Mangifera indica). Soil-root samples had large roots separated by sieving (min. 2 mm aperture) and soil DNA extractions made on the sieved soil containing fine root fragments that had passe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This patchiness most likely also results from the reduced DNA persistence in tropical rainforest soils due to high demands of the living biomass for phosphorus, which is otherwise highly limitating (Dalling et al 2016), thus reducing the probability of detecting large organisms. Accordingly, experiments show that dead root DNA is almost totally degraded after 15 days (Bithell et al 2014). Likewise, microbes and soil fauna communities exhibit marked seasonal and yearly dynamics (Fragoso & Lavelle 1992;Kivlin & Hawkes 2016b;Kivlin & Hawkes 2016a;Pajares et al 2018), and so most likely does their DNA as compared to that of rooted plants, which continuously release DNA in soils (Figure 2D).…”
Section: Constraints and Limitsmentioning
confidence: 96%
“…This patchiness most likely also results from the reduced DNA persistence in tropical rainforest soils due to high demands of the living biomass for phosphorus, which is otherwise highly limitating (Dalling et al 2016), thus reducing the probability of detecting large organisms. Accordingly, experiments show that dead root DNA is almost totally degraded after 15 days (Bithell et al 2014). Likewise, microbes and soil fauna communities exhibit marked seasonal and yearly dynamics (Fragoso & Lavelle 1992;Kivlin & Hawkes 2016b;Kivlin & Hawkes 2016a;Pajares et al 2018), and so most likely does their DNA as compared to that of rooted plants, which continuously release DNA in soils (Figure 2D).…”
Section: Constraints and Limitsmentioning
confidence: 96%
“…It has been shown for subterranean clover ( Trifolium subterraneum L) and ryegrass ( Lolium perenne L.) that RDD accurately describes different masses of root tissue added to a given amount of soil (Riley et al, ). For mango ( Mangifera indica L.), it was shown that using RDD is suitable to distinguish between different soil depths (Bithell et al, ). Considering utilization of RDD in research and breeding, Huang et al () showed significant genotypic variation for RDD in wheat ( Triticum aestivum L.) and heritability for RDD between 50% and 90% across several field locations in Australia.…”
Section: Introductionmentioning
confidence: 99%